Physical and physiological demands of elite team handball players - Barbero, J. C.; Granda-Vera, J.; Calleja-Gonzalez, J.; Del Coso, J. (International Journal of Performance Analysis in Sport, 2014)
The aim of this study was to analyse physical and physiological demands of elite team handball players. Nineteen men from a professional handball team played a simulated 30-min match in an outdoor sport facility. Instantaneous speed during the games was assessed using GPS devices and the number of body-impacts above 5-g was measured by accelerometry. Individual heart rate was also measured by using heart rate monitors. Handball players covered 94.0±7.7 m/min during the simulated match with a mean of 82.5±4.7 % of maximal heart rate. The average speed of the wingmen was significantly higher than pivots, centres and backcourt players (102.5±1.8 vs. 94.4±4.6, 92.6±1.0 and 86.1±6.0 m/min, respectively; P<0.05). Running pace at sprint speed (e.g.,<18 km/h) was on average 2.4±2.3 m/min but it was significantly higher in wingmen than in the remaining playing positions (4.5±2.4 vs 0.5±0.1, 2.4±1.7 and 1.3±1.0 m/min, respectively; P<0.05). The overall number of body-impacts was 13.6±7.7 per min of game with pivots being the players that presented the highest values (17.2±5.7 impacts/min; P<0.05). Physical demands of elite handball are primarily related to high-intensity actions, impacts and rapid recovery during the game. The training of elite handball players should be specific to the exercise actions performed during the game.